(untitled) (Eurasian Medical Research Periodical, 2022)
Rheumatoid arthritis is a chronic inflammatory disease characterized by progressive damage of synovial-lined joints and variable extra-articular manifestations. Infliximab is a chimeric monoclonal antibody to human tumor necrosis factor- α.It has been used as an effective treatment in rheumatoid arthritis because of its substantial benefits on the signs and symptoms of the disease, as well as its ability to significantly retard the radiographic progression of joint damage.